Use of Cucurbit[6]uril as Ionophore in Ion Selective Electrodes for Etilefrine Determination in Pharmaceuticals. Issue 11 (11th July 2019) - Gomes Amorim, Célia; Araújo, Alberto; da Conceição Montenegro, Maria
Abstract: Cucurbiturils are macrocyclic molecules and have been used with promising results in the development of electrochemical sensors and biosensors due to their main properties such as shape, selectivity, binding interactions and solubility. However, its application for the development of ion selective electrodes has been scarce. In this work, cucurbit[6]uril was used as molecular‐recognition compound for etilefrine sensing membrane with potentiometric transduction. The etilefrine selective electrode was evaluated and proposed as an alternative methodology for pharmaceutical quality control. Different membranes composition were evaluated, considering the use of different solvent mediators and the presence of anionic additives. The best membrane comprises 9.24 mmol.Kg −1 of cucurbit[6]uril, 68.90 % (w/w) of dibutylsebacate and 30.18 % (w/w) of carboxylated polyvinyl chloride. The electrode exhibited selective cationic response toward the etilefrine in a concentration interval of more than four decades, with an slope of 57.4±0.5 mV dec −1, a practical detection limit of (8±1)×10 −7 mol L −1 and a low limit of linear range of (1.25±0.28)×10 −6 mol L −1 . The selectivity of the electrode towards different interfering was high. A comparative evaluation of the accuracy and precision of both procedures was done using the t‐student test (t4, 12=1.135) and the Fischer test (F12, 4=2.42) and compared with the tabulated ones (t4, 12=1.135, F11, 3=5.91) for the level of confidence of 95 %. Abstract :